2016
DOI: 10.2147/cia.s111927
|View full text |Cite
|
Sign up to set email alerts
|

Tai chi qigong as a means to improve night-time sleep quality among older adults with cognitive impairment: a pilot randomized controlled trial

Abstract: PurposeAge-related cognitivee decline is a growing public health concern worldwide. More than a quarter of adults with cognitive impairment experience sleep disturbance. The objective of this pilot study was to evaluate the preliminary effects of tai chi qigong (TCQ) on improving the night-time sleep quality of older adults with cognitive impairment.ParticipantsOlder adults with cognitive impairment who complain of sleep disturbance.MethodsA randomized controlled trial with two groups. Fifty-two subjects were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 27 publications
3
61
0
2
Order By: Relevance
“…The results of this study showed that the Physical Activity Program increased their cognitive functions and sleep quality. These findings directly support those from previous studies, physical activity interventions such as yoga, tai chi qigong, 12 weeks and pedometer‐based walking exercise, and cognitive exercise program, aquatic exercise have also improved self‐reported sleep quality in addition to cognitive function in older adults.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The results of this study showed that the Physical Activity Program increased their cognitive functions and sleep quality. These findings directly support those from previous studies, physical activity interventions such as yoga, tai chi qigong, 12 weeks and pedometer‐based walking exercise, and cognitive exercise program, aquatic exercise have also improved self‐reported sleep quality in addition to cognitive function in older adults.…”
Section: Discussionsupporting
confidence: 88%
“…People with a mild version may demonstrate changes in their cognitive functions, but without affecting their daily activities. More than a quarter of older adults with cognitive impairment experience sleep disturbance . A study examining the epidemiology of sleep disturbances in the elderly found that the rate of sleep disturbances in the elderly sometimes reaches up to 50% .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tai chi and qigong can be combined to enhance the training effect, and form an activity that engages the mind and the body, the engagement of the mind particularly leading to meditative quality and preventing boredom 18. Research has demonstrated that tai chi and qigong have beneficial effects on patients with respiratory disease,13,19 heart disease,20,21 metabolic control in type-2 diabetes,22 high blood pressure,23 emotional stress,24 and sleep disturbances in older adults 25. With the favorable results of previous studies, the applicably of tai chi qigong to the hidden elderly deserves special attention.…”
Section: Introductionmentioning
confidence: 99%